Osteoclasts Lose Innate Inflammatory Reactivity to Metal and Polymer Implant Debris Compared to Monocytes/Macrophages - Yadav, Jessica (Bentham Open, 2013)
Long-term aseptic failures of joint replacements are generally attributed to implant debris-induced inflammation and osteolysis. This response is largely mediated by immune and bone cells (monocytes/macrophages and osteoclasts, respectively), that in the presence of implant debris (e.g. metal particles and ions), release pro-inflammatory cytokines such as IL-1β, TNF-α, and IL-6. The relative degree to which implant debris can illicit inflammatory response(s) from osteoclasts vs monocytes/macrophages is unknown, i.e. are osteoclasts a viable target for anti-inflammatory therapy for implant debris? We investigated relative monocyte versus osteoclast inflammatory responses in a side-by-side comparison using implant debris from the perspective of both danger signaling (IL-1β) and pathogenic recognition (TNF-α) reactivity (Challenge Agents: Cobalt-alloy, Titanium-alloy, and PMMA particles, 0.9-1.8um-dia ECD and Cobalt, and Nickel-ions 0.01-0.1mM, all with and without LPS priming). Human monocytes/macrophages reacted to implant debris with >100 fold greater production of cytokines compared to osteoclast-like cells. Particulate Co-alloy challenge induced >1000 pg/ml of IL-1β and TNF-α, in monocytes and <50pg/mL IL-1β and TNF-α in osteoclasts. Cobalt ions induced >3000pg/mL IL-1β and TNF-α in monocytes/macrophages and <50pg/mL IL-1β and TNF-α in osteoclasts. The paracrine effect of supernatants from debris-treated monocytes/macrophages was capable of inducing greater osteoclastogenesis (TRAP+, p<0.06) and inflammation than direct debris challenge on osteoclasts. Our results indicate that as monocytes/macrophages differentiate into osteoclasts, they largely lose their innate immune reactivity to implant debris and thus may not be as relevant a therapeutic target as monocytes/macrophages for mitigating debris-induced inflammation.